Perceived social support in adults with autism spectrum disorder and attention‐deficit/hyperactivity disorder. Issue 5 (3rd March 2017) - Alvarez‐Fernandez, Sonia; Brown, Hallie R.; Zhao, Yihong; Raithel, Jessica A.; Bishop, Somer L.; Kern, Sarah B.; Lord, Catherine; Petkova, Eva; Di Martino, Adriana
Abstract : Perceived social support (PSS) has been related to physical and mental well‐being in typically developing individuals, but systematic characterizations of PSS in autism spectrum disorder (ASD) are limited. We compared self‐report ratings of the multidimensional scale of PSS (MSPSS) among age‐ and IQ‐matched groups of adults (18–58 years) with cognitively high‐functioning ASD ( N  = 41), or attention‐deficit/hyperactivity disorder (ADHD; N  = 69), and neurotypical controls (NC; N  = 69). Accompanying group comparisons, we used machine learning random forest (RF) analyses to explore predictors among a range of psychopathological and socio‐emotional variables. Relative to both ADHD and NC, adults with ASD showed lower MSPSS ratings, specifically for the friends subscale (MSPSS‐ f ). Across ASD and ADHD, interindividual differences in autism severity, affective empathy, symptoms of anxiety related to social interactions, hyperactivity/impulsivity, and somatization best predicted MSPSS‐ f . These relationships did not differ between clinical groups. While group comparisons demonstrated greater impairment in individuals with ASD, analyzing individuals' characteristics revealed cross‐diagnoses similarities in regard to their MSPSS‐ f relationships. This is consistent with the Research Domain Criteria framework, supporting a trans‐diagnostic approach as on the path toward "precision medicine." Autism Res 2017, 10: 866–877 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.